Tuning the Electron Localization of Gold Enables the Control of Nitrogen-to-Ammonia Fixation - Zheng, Jianyun; Lyu, Y.; Qiao, M.; Veder, Jean P; Marco, Roland D.; Bradley, J.; Wang, R.; Li, Y.; Huang, A.; Jiang, San Ping; Wang, S. (WILEY-V C H VERLAG GMBH, 2019)
The (photo)electrochemical N2 reduction reaction (NRR) provides a favorable avenue for the production of NH3 using renewable energy in mild operating conditions. Understanding and building an efficient catalyst with high NH3 selectivity represents an area of intense interest for the early stages of development for NRR. Herein, we introduce a CoOx layer to tune the local electronic structure of Au nanoparticles with positive valence sites for boosting conversion of N2 to NH3. The catalysts, possessing high average oxidation states (ca. 40 %), achieve a high NH3 yield rate of 15.1 μg cm−2 h−1 and a good faradic efficiency of 19 % at −0.5 V versus reversible hydrogen electrode. Experimental results and simulations reveal that the ability to tune the oxidation state of Au enables the control of N2 adsorption and the concomitant energy barrier of NRR. Altering the Au oxidation state provides a unique strategy for control of NRR in the production of valuable NH3.